Effect of Annealing Temperatures on Formability of SS 304 tubes during Tube Hydroforming Process: A Numerical study - Pathapalli, Venkateshwar Reddy; Veerabhadra Reddy Basam,; Janaki Ramulu Perumalla, (International Journal of Integrated Engineering, 2020)
Tube hydroforming is an advanced manufacturing process which utilizes a liquid medium to deform the tube with required shape. This method has an advantage of attaining uniform pressure throughout the tube at any time during the process. The main aim of the present study was to know the effect of different annealing temperatures on the tube hydroforming of SS 304 steel. Specimens were annealed with four different temperatures, viz., 100oC, 150oC, 200oC and 250oC. Annealed samples were tested to find the tensile properties in terms of yield strength, strength coefficient, strain hardening exponent, elongation and ultimate tensile strength. The evaluated mechanical properties were utilized to run the tube hydroforming simulations using finite element code. Effects of annealing temperatures on bulge height and thickness distribution of the bulged area of the tube were studied using FEM. Numerical simulations confirmed that the annealing temperatures had an effect on the bulge height and thickness distribution in the bulged zone of the tube.